Workplace equality and diversity in Iceland : organizational efforts and influence on employees - Laura Nesaule 1984- (2016)
The aim of this study was to determine whether management intentions to enhance or manage equality and diversity in organizations positively influences employee perceptions of equality, diversity, justice and trust. Participants in the study in phase one were 35 human resource managers in Icelandic organizations with 70 or more employees. In phase two, 1041 employees within the same organizations participated. The measurement used for phase one was designed by The Research Center for Human Resource Management at Reykjavík University and is based on the Strategic Human Resource Management (SHRM) maturity scale developed by Paul Kearns (2005). The measurement for phase two included constructs designed to assess employee perceptions of equality, diversity, justice and trust. Results revealed no relationship between the existence of equality statements and employees’ perceptions of equality, diversity, justice or trust, but there were significant relationships between the existence of diversity statements and employees’ perceptions of equality. Both organizations’ intentions in terms of acquiring equal wage certification and equality maturity had a positive and significant relationship with employee perceptions of equality. Overall, Strategic Human Resource Management maturity was significantly related to employee-perceived equality, diversity and trust scores. Markmið þessarar rannsóknar er að skoða hvort fyrirætlanir stjórnunina til að auka eða stjórna jafnrétti og fjölbreytni í skipulagi sé jákvæð áhrif á skynjun starfsmanna vegna jafnréttis, fjölbreytileika, réttlæti og traust. Þátttakendur í rannsókninni í fyrsta áfanga voru 35 mannauðsstjórar í íslenskum stofnunum með 70 og fleiri starfsmenn. Í áfanga tvö 1041 starfsmenn innan sömu stofnunum tóku þátt. Mælingin sem er notað í fyrsta áfanga var hannað af starfsmönnum hjá Rannsóknarmiðstöðvar í mannauðsstjórnun við Háskólann í Reykjavík og það er byggt á þroskastigi mannauðstjórnar (Human Resource maturity scale) þróað af Paul Kearns (2005). Mælingin fyrir ...